Imunitas Tubuh terhadap Cytomegalovirus (CMV) - Farida Juliantina Rachmawaty; Linda Rosita (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2002)
Cytomegalovirus (CMV) infection has been an important health prob-lem recently. The impact of the infection on the fetus i.e. physical disability and mental retardation will decrease the quality of life. Hence, this will influ¬ence the quality of the next generation, as well as becoming a burden of the family and the community. The expensive cost for its laboratorium examamination and therapy has caused some problems. It is therefore, it is important to understand the body immunity toward this viral infection. Cytomegalovirus (CMV) constitutes Herpesviridae family group. This virus has spread around the world, although its replication develops slowly. Cytomegalovirus (CMV) does not stand high temperature and its reservoar is only human. The transmission of this virus needs frequent contacts and inti¬mate relationship with the infected person. A healthy person with good immu¬nity condition is not easily infected by CMV. However, it needs special atten¬tion on susceptible groups i.e. pregnant women with the fetuses they are carrying; and children, as well as humans with bad immunity or who receive organ tranplantation. This infection rarely becomes mononucleosis syndrom. The diagnostic pro-cedure for adult patients are more frequently based on serologic examinations rather than the clinical conditions. The therapy for the CMV infection patient with intra venous Ganciclovir shows good result. Other recommended thera-pies are intra venous Foscarnet and Cidovir, however, they need caution due to their high side effects.Infeksi Cytomegalovirus (CMV) merupakan masalah penting akhir-akhir ini. Dampak yang ditimbulkan pada janin yang terinfeksi berupa kecacatan fisik dan retardasi mental akan menurunkan kualitas hidupnya. Hal ini akan berpengaruh pula terhadap generasi penerus, serta menjadi beban keluarga dan masyarakat. Mahalnya pemeriksaan laboratorium dan pengobatan menimbulkan masalah tersendiri. Dengan demikian perlu diketahui imunitas tubuh terhadap virus ini. Cytomegalovirus (CMV) merupakan kelompok virus dari famili Herpesviridae. Virus ini tersebar di seluruh dunia, namun replikasinya berkembang dengan lambat. CMV tidak tahan terhadap pemanasan dan satu-satunya reservoar adalah manusia. Perlu kontak yang berulang-ulang dan hubungan yang erat dengan penderita untuk dapat tertular virus ini. Pada orang sehat dengan kondisi imunitas yang bagus tidak mudah terinfeksi CMV. Diperlukan perhatian khusus pada kelompok-kelompok yang rentan, yaitu ibu hamil dengan janin yang dikandungnya dan anak-anak, demikian pula pada individu yang jelas-jelas diketahui terjadi penurunan imunitas atau mendapat tranplantasi organ. Infeksi CMV jarang menjadi sindrom mononukleosis. Diagnosis pada orang dewasa lebih banyak ditegakkan berdasar pemeriksaan serologis daripada gejala klinik. Terapi pada penderita dengan Ganciclovir intra vena menunjukkan hasil yang baik. Terapi lain yang dapat direkomendasi adalah Foscamet dan Cidovir intra vena, namun perlu hati-hati karena efek samping yang tinggi.